¿How important is ethics in the development of activities of public servants? (2016)
The present study was to analyze conceptually the importance of public ethics in the development of all activities of a public servant; the importance of this work is based on that there is a global problem not only in The present study was to analyze conceptually the importance of public ethics in the development of all activities of a public servant; the importance of this work is based on that there is a global problem not only in Colombia where there have been several cases of corruption, because of this society questions the behavior and actions of different political actors and / or public officials.